Effects and mechanism of dehydroepiandrosterone on epithelial–mesenchymal transition in bronchial epithelial cells. (1st June 2014) - Xu, Li; Xiang, Xudong; Ji, Xiaoying; Wang, Wenjing; Luo, Min; Luo, Shuangling; Li, Keng; Gong, Subo; Liu, Shaokun; Ma, Libing; Chen, Ping; Li, Jinxiu
ABSTRACT Background: Chronic persistent asthma is characterized by airway remodeling, in which epithelial–mesenchymal transition (EMT) may play a significant role. Dehydroepiandrosterone (DHEA), a steroid hormone and testosterone analog, is considered as an important immunomodulating hormone. However, its role in EMT remains unclear. We sought to investigate whether transforming growth factor-β1 (TGF-β1) stimulates human bronchial epithelial cells (16HBE-14o) to undergo EMT, and whether this transition can be abrogated by DHEA. Methods: The 16HBE-14o cells were stimulated with 5 ng/ml TGF-β1 for 3 days to induce EMT, with or without DHEA pretreatment, and assayed for epithelial or mesenchymal markers using Western Blot. The involvement of phosphoinositide 3-kinase (PI3K) -mediated signaling pathway was also evaluated, the epithelial cells were also incubated with pharmacological approaches (agonists and antagonists of Akt, LY294002 or IGF-1) or flutamide, the antagonist of androgen receptor. Results were analyzed using nonparametric statistical tests. Results: Our data demonstrate that treatment of 16HBE-14o cells with TGF-β1 for 3 days induced EMT as reflected by conversion to the spindle-like morphology, loss of E-cadherin, and acquisition of a-smooth muscle actin (a-SMA). Pretreatment of 16HBE-14o cells with DHEA preserved the epithelial-like morphology, restored the expression of E-cadherin, and abolished the activation of a-SMA, and this effect is a PI3K-dependent mechanism. Conclusion: Our results indicate that TGF-β1 induces EMT in a PI3K-dependent manner in 16HBE-14o cells. DHEA inhibits the bronchial epithelial to mesenchymal transition via the inhibition of PI3K/Akt-dependent signal pathway stimulated by TGF-β1. Therefore, DHEA may be a useful therapy for asthma.